INVENTARISASI TANAMAN JELUTUNG (DYERA COSTULATA HOOK) SEBAGAI TUMBUHAN LANGKA YANG TERDAPAT DI ARBORETUM UNIVERSITAS RIAU - Zul Ningsi; M. Mardhiansyah '; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Dyera costulata Hook is one of the priority tree species that have a high enough potensial to be developed, because wood of Dyera costulata Hook has a high economic value and its existence is endangered. Based on threat category of population according to the IUCN, species of Dyera costulata Hook included in the category nearly threatened. Arboretum is one type of ex-situ conservation. Ex-situ conservation purpose is to protect and preserve the species, especially the flora and fauna that are rare. Purpose of the implementation of this study was to determine the availability, amount and dominance of Dyera costulata Hook found in the arboretum of Riau University. Techniques of data collection is done by using the census method. The results showed that there are only 3 rods Dyera costulata Hook (0,17 %) whereas 1.789 rods (99,83 %) is a type of non jelutung. INP at a rate of 0 % seedling, sapling rate of 0 %, 1,15 % for poles rate and tree level of 0 %. Keywords : inventore, rare, Dyera costulata Hook, arboretum.